MORPHOLOGICAL TYPOLOGY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Morphological typology is a branch of linguistics that classifies languages according to how they form words and express grammatical relationships. It examines the internal structure of words, including the use of affixes, stem changes, and the degree to which words combine multiple meanings. Traditionally, languages are grouped into several main types: isolating, which use minimal morphology; agglutinative, which attach clearly separable affixes; fusional, where a single affix can encode multiple grammatical features; and polysynthetic, which build complex words that may represent entire sentences. Although few languages fit perfectly into only one category, these types help linguists compare patterns across languages and understand how morphology reflects broader grammatical and historical processes. Morphological typology therefore provides important insights into linguistic diversity, language evolution, and the way humans encode meaning in word structure.